1990
DOI: 10.1177/002221949002300114
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the DISTAR Reading Program for Children with Learning Disabilities

Abstract: The reading achievement of students with learning disabilities who received reading instruction through the DISTAR program was compared to that of similar students using basal reader materials. The overall reading scores of the groups were not significantly different following 1 and 2 years of instruction, although students in the DISTAR program had somewhat better word attack skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 5 publications
0
6
1
Order By: Relevance
“…Other studies have not found such achievement gains (Kuder, 1990;Ogletree, 1977;Serwer, Shapiro, & Shapiro, 1973), and still others have found more isolated benefits on specific reading subscales (Kuder, 1990). We have found no research, however, examining the reading motivational effectiveness of this program.…”
Section: Distarcontrasting
confidence: 53%
“…Other studies have not found such achievement gains (Kuder, 1990;Ogletree, 1977;Serwer, Shapiro, & Shapiro, 1973), and still others have found more isolated benefits on specific reading subscales (Kuder, 1990). We have found no research, however, examining the reading motivational effectiveness of this program.…”
Section: Distarcontrasting
confidence: 53%
“…These students were part of a larger sample of 48 students who had participated in an earlier study of the Distar reading program (Kuder, 1990). The subject sample for the present study consisted of all students from the original study who had remained in the district for the 2 years of this study and who continued to receive their reading instruction in a self-contained special education classroom.…”
Section: Methods Subjectsmentioning
confidence: 99%
“…Although some studies have found very positive results (e.g., Gregory, Hackney, & Gregory, 1982; L'E. Stein & Goldman, 1980;Summerell & Brannigan, 1977), others have found limited success with the use of direct instruction reading programs such as Corrective Reading (Polloway, Epstein, Polloway, Patton, & Ball, 1986) and Distar (Kuder, 1990).…”
mentioning
confidence: 99%
“…These results have appeared with the general student population (e.g., Becker & Carnine, 1980;O'Brien & Ware, 2002;Stebbins, St. Pierre, Proper, Anderson, & Cerva, 1977;Vitale & Joseph, 2008) and with students with disabilities. Studies have demonstrated the effectiveness of DI reading programs with students with learning disabilities (Benner, 2007;Benner, Kinder, Beaudoin, Stein, & Hirschmann, 2005;Cooke, Gibbs, Campbell, & Shalvis, 2004;Kuder, 1990Kuder, , 1991Malmgren & Leone, 2000;Scarlato & Asahara, 2004), students with intellectual disabilities (Flores, Shippen, Alberto, & Crowe, 2004;Haring & Krug, 1975;Maggs & Morath, 1976;Malmgren & Leone, 2000;Riepl, Marchand-Martella, & Martella, 2008), children who demonstrate developmental delays (Flores & Ganz, 2007;Riepl et al, 2008), and students identified with emotional disturbance (Benner, 2007;Cook et al, 2004;Malmgren & Leone, 2000;Scarlato & Asahara, 2004;Strong, Wehby, Falk, & Lane, 2004). Additionally, DI reading programs have been effectively implemented outside of traditional elementary schools in a variety of settings, including middle schools (Dowdell, 1996;Grossen, 2004;Lewis, 1982;Shippen, Houchins, Steventon, & Sartor, 2005), high schools (Harris, Marchand-Martella, & Martella, 2000;Marchand-Martella, Martella, Orlob, & Ebey, 2000), a residential treatment center (Scarlato & Asahara, 2004), alternative schools (Steventon & Fredrick, 2003), and juvenile corrections facilities (Drakeford, 2002;Houchins, ...…”
Section: The Effectiveness Of Direct Instructionmentioning
confidence: 99%